Neoliberal populism and governmentality in Turkey: The foundation of communication centers during the AKP era. (May 2018) - Boyraz, Cemil
This article is based on the question "How does the current governing party in Turkey, namely Justice and Development Party (Adalet ve Kalkınma Partisi, AKP), reproduce its social power?" In order to answer this question, it is suggested that a combination of the different techniques of governmentality of the ruling party should be analyzed, with particular reference to the policies and institutions reconfiguring the role of the state and the notion of public deliberation in the midst of the rising discontents of neoliberalism in Turkey. As an instance of such a technique of neoliberal governmentality in populist content, the formation of the communication centers by the AKP in Turkey will be investigated. For this purpose, firstly, the rise of the populism will be related to the increasing need for channels of political participation and a solution to public demands in the midst of rising authoritarian tendencies, in order to solve the political legitimacy crisis as well as creating new forms of representation for the politically excluded masses. Then, secondly, the main cornerstones of the AKP populism will be analyzed and the formation and the future of the communication centers as a particular case will be discussed in details. Lastly, it will be argued that those centers do not only reflect the populist concerns of the governing party but also serve as a crucial source of electoral success, as well as managing tensions stemming from the neoliberal configuration of the public sphere and state–citizen relations.